“If you have light, your heart will be at peace”: A qualitative study of household lighting and social integration in southwestern Uganda - Ponticiello, Matthew; Nuwagira, Edwin; Tayebwa, Mellon; Mugerwa, Joseph; Nahabwe, Hellen; Nakasita, Catherine; Tumuhimbise, John Bosco; Lam, Nicholas L; Wiens, Matthew O; Vallarino, Jose; Allen, Joseph G; Muyanja, Daniel; et al. (Journal of Global Health, 2023)
Background: Expanding electrification and access to other clean and affordable energy, such as solar energy, is a critical component of the Sustainable Development Goals, particularly in sub-Saharan Africa where 70% of people are energy insecure. Intervention trials related to access or less polluting household energy alternatives have typically focused on air quality and bi¬ological outcomes rather than on how an intervention affects the end user’s lived experiences, a key determinant of uptake and adoption outside of a research setting. We explored per¬ceptions of and experiences with a household solar lighting in¬tervention in rural Uganda. Methods: In 2019, we completed a one-year parallel group, randomized wait-list controlled trial of indoor solar lighting systems (ClinicalTrials.gov NCT03351504) in rural Uganda where participants are largely relying on kerosene and other fu¬el-based lighting received household indoor solar lighting sys¬tems. In this qualitative sub-study, we conducted one-on-one, in-depth qualitative interviews with all 80 female participants enrolled in the trial. Interviews explored how solar lighting and illumination impacted participants’ lives. We applied a theo¬retical model linking social integration and health to analyse dynamic interactions across aspects of study participants’ lived experiences. Sensors were used to measure daily lighting use before and after receipt of the intervention solar lighting system. Results: Introduction of the solar lighting system increased dai¬ly household lighting use by 6.02 (95% confidence intervals (CI) = 4.05-8.00) hours a day. The solar lighting intervention had far-reaching social implications with improved social in¬tegration and, consequently, social health. Participants felt that lighting improved their social status, mitigated the stigma of poverty, and increased the duration and frequency of social interactions. Household relationships improved with access to lighting because of reduced conflicts over light rationing. Par¬ticipants also described a communal benefit of lighting due to improved feelings of safety. At the individual-level, many re¬ported improved self-esteem, sense of well-being, and reduced stress. Conclusion: Improved access to lighting and illumination had far reaching implications for participants, including improved social integration. More empirical research, particularly in the light and household energy field, is needed that emphasizes the impacts of interventions on social health.
Keywords: Household lighting; Social integration; Electricity; Uganda